Challenges of tax revenue generation in developing countries: adopting the carrot and stick approach - Umar, Mohammed Abdullahi; Derashid, Chek; Ibrahim, Idawati (IOSR, 2017)
The study reiterates the challenges of tax revenue generation in developing countries.While the advanced countries have traditionally performed well in tax revenue generation, developing countries continue to perform poorly. This accounts for the economic development challenges faced by these countries.The study identifies tax noncompliance as a key factor for the current under performance of tax revenue in developing countries.However, there are over sixty variables associated with tax noncompliance in existing literature and this could lead to confusion in the effort to tackle noncompliance.There is need to streamline existing variables by identifying the key ones in the context of developing countries. This study advocates for the carrot and stick model in tackling the challenges of tax compliance in developing countries.The study further identifies socioeconomic condition, citizen engagement and tax service quality as constituting the carrot factors while audit and sanction constitute the stick factors. It argues that an optimal mix of the carrot and stick factors will go a long way in tackling the tax revenue challenges of developing countries.